From spheroids to organoids: next-generation models for CAR-T cell therapy research in solid tumors - Jassin, Mégane; Block, Alix; Désiront, Laury; Vrancken, Louise; Grégoire, Céline; Baron, Frédéric; Ehx, Grégory; Nguyen, Thi Tham; Caers, Jo (Frontiers in Immunology, 2025)
Chimeric Antigen Receptor T-cell (CAR-T) therapy is a revolutionary immunotherapy involving the genetic modification of T cells to express chimeric receptors targeting specific tumor antigens. Over the past decade, CAR-T therapy has significantly advanced with the development of five generations of CAR-T cells, each introducing modifications to enhance T cell efficacy, persistence, and the ability to overcome immune evasion mechanisms. The manufacturing of CAR-T cells has also evolved, employing techniques such as viral vector transduction or CRISPR-based gene editing, lipid nanoparticle, or transposon mediated approaches, to optimize their function. However, the development of CAR-T therapy for solid tumors faces significant challenges, primarily due to the hostile tumor microenvironment (TME), which traditional two-dimensional (2D) culture systems fail to accurately replicate. This review explores the potential of three-dimensional (3D) culture models, including spheroids and organoids, as tools for studying CAR-T cells in the context of solid tumors. Unlike 2D models, 3D systems offer a more physiologically relevant environment, better mimicking the TME, tumor heterogeneity, and immune interactions which CAR-T cells must encounter. We examine the advantages and limitations of 2D versus 3D models and discuss four key methods for generating spheroids/organoids: direct cell aggregation, scaffold-based, microfluidic, organs-on-chip and bioprinting, and patient-derived organotypic tumor approaches. Moreover, we explore the use of murine models in preclinical CAR-T research, highlighting their role in studying the dynamics of CAR-T cell trafficking, efficacy, and off-target effects. While CAR-T therapy has shown impressive success in some hematological malignancies, there is still a critical need for improved models to study CAR-T efficacy against solid tumors, particularly in relation to the TME. 2D models remain a valuable tool but should be combined with 3D models and in vivo murine studies for more accurate clinical outcome predictions. As we advance toward preclinical and clinical applications, ongoing efforts to develop and refine 3D culture systems are essential for overcoming the unique challenges of CAR-T therapy in solid tumors.